A privacy protection scheme for telemedicine diagnosis based on double blockchain. (September 2021) - Wang, Wei; Wang, Lianhai; Zhang, Peijun; Xu, Shujiang; Fu, Kunlun; Song, Lianxin; Hu, Shanshan
Abstract: With the development of the electronic healthcare industry, telemedicine diagnosis (TMD) has become a more flexible and convenient way. In the general remote diagnosis scheme, the collected medical data is stored in the cloud which may be leaked or tempered with. Since blockchain has the characteristics of centralized storage, some schemes employ blockchains to overcome the security problem of cloud storage, but most of them lack a supervision mechanism. The identity information provided by the doctor to the user must be accurate. However, the digital certificate issued by the certificate authority (CA) may have the problem of information update latency. To solve the above questions, we propose DBTMD, a TMD privacy protection scheme based on double blockchain. We have constructed two types of blockchains, Userchain and Medicalchain, and designed five transactions. Users, doctors, and hospitals can implement secure data interaction, and hospitals can supervise doctors effectively. We have developed an identity authentication chain to ensure the real-time accuracy of the doctor's identity information. Security analysis and experimental analysis show that our scheme greatly reduces the communication costs of keys' transaction compared with existing schemes.